The use of flashcard media in English learning topic knowing numbers in class 1c students at SDITA El Mamur school - Elma Rida Yuliana (Mitra Palupi, 2022)
Background: English subjects at the SD/MI level emphasize the introduction of vocabulary as a foundation or basis in learning English. English ability can be seen from the wealth of vocabulary that a person has. One of the creative efforts in making learning interesting is using media flash cards. Purpose: This study aims to determine the application of flashcards media about numbers in English in grade 1C at SDITA EL MAMUR. Design and methods: The researcher collected data using a qualitative approach, the type of research was descriptive narrative, and the data collection technique was interviews with informants, namely the homeroom teacher of class 1C. at SDITA EL MAMUR. Results: The results of this study indicate that the use of flashcard media can assist students in pronouncing vocabulary numbers in English because the use of flashcard media is easy to understand and attractive to students.